Dosagem de hormônios esteroides sexuais em camada de gordura subcutânea de toninha, Pontoporia blainvillei (Cetartiodactyla; Pontoporiidae), do litoral de São Paulo, Brasil. - Ribeiro, Vanessa Lanes (2019)
The Franciscana dolphin (Pontoporia blanvillei) is a small odontocete impacted by anthropic activities (bycatch, habitat degradation). The hormonal measurement in biological matrices (feces, urine, blubber, milk, saliva, blow) has been increasingly used in aquatic mammals for certain reproductive parameters. The present study validated the method of extraction and measurement of testosterone and progesterone in blubber kept in two different temperatures (-20°C and -196°C), besides correlating the hormone concentration with gender, sexual maturity, age, stage of development, body length and occurrence of pregnancy. The carcasses were collected from stranded and bycatch dolphins of the coast of São Paulo. Blubber samples were collected and frozen at -20°C (n=101) and -196°C (liquid nitrogen) (n=28). The extraction was performed with a method described in literature and the hormonal analyses were done by enzyme immunoassay for the two hormones. An analysis was performed on two units of hormone concentration (ng/g and ng/mg). The inter-assay coefficient of variation was 6.89% for progesterone and 1.67% for testosterone, the intra-assay coefficient of variation was 7.82% for progesterone and 3.29% for testosterone. The progesterone assay presented parallelism F1.5= 0.87, p= 0.45 and testosterone presented F1.5= 3.79, p= 0.11. The mean extraction efficiency was 66% for progesterone and 70% for testosterone. The method of extraction and hormonal analysis was feasible for Pontoporia blainvillei. No difference was found between the progesterone and testosterone levels of samples kept at the two storage temperatures in both measurement units. The levels of hormones found were in agreement with the expectation that progesterone levels higher than males, mature and adults were higher than immature, juvenile and calf, were not abandoned with age and the same conclusions were obtained for males in relation to a testosterone. As pregnant also the levels of progesterone are higher than the rest of the specimens. High calf and fetuses hormones, which may be a reflection of the maternal hormonal circulation, besides the rate of incorporation of hormones or the more effective extraction.